1990
DOI: 10.1111/j.1756-1051.1990.tb00546.x
|View full text |Cite
|
Sign up to set email alerts
|

Thalloconidia in the genus Umbilicaria

Abstract: Hestmark. G . 1990. Thalloconidia in the genus Umhilicoria. -Nord. J . Bot. Y: 547-574. Copenhagen. ISSN 0107-055X.Hypothalline, hyphomycetous anamorphsthalloconidiafrom 18 taxa in the lichen genus Umhilicaria have been studied in detail with the aid of scanning and transmission electron microscopy. These asexual propagules are brown to dark brown, singleto multi-cellular (up to 2500 cclls), spherical to irregular, smooth to rugged; their walls two-or three-layered. The thalloconidia are produced and seceded d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
2

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 11 publications
(10 reference statements)
1
30
0
2
Order By: Relevance
“…They are most frequently found in the genus Umbilicaria Hoffm. (Hestmark 1990) but have also been reported in Protoparmelia M. Choisy, Rhizoplaca Zopf and Sporastatia A. Massal. (Poelt & Obermayer 1990).…”
Section: Mycobank No: Mb805057mentioning
confidence: 87%
“…They are most frequently found in the genus Umbilicaria Hoffm. (Hestmark 1990) but have also been reported in Protoparmelia M. Choisy, Rhizoplaca Zopf and Sporastatia A. Massal. (Poelt & Obermayer 1990).…”
Section: Mycobank No: Mb805057mentioning
confidence: 87%
“…Thallus sections were cut by a freezing microtome, 5, 10 or 15 μm thick, and mounted in lactophenol cotton blue. Thalloconidia (Hestmark , ) were examined in thin sections and photomicrographed using a scanning electron microscope (SEM). DNA from some of the Ecuador specimens have previously been sequenced in the context of a study of the endemic central Andean Umbilicaria element (Hestmark et al ), and the specimen number, type of sequences and GenBank accession numbers are provided.…”
Section: Methodsmentioning
confidence: 99%
“…Nyl. Nonetheless Hestmark (1990) showed that the species is distinct from the aforementioned species in that the asexual thalloconidia (anamorphs) generated on the lower side of U. nylanderiana are unicellular while those of U. polyphylla are multicellular, and that neither U. hyperborea nor U. arctica produce thalloconidia but solely rely for their propagation on sexually generated ascospores from apothecia. In a study of the teleomorph-anamorph relationships in Umbilicaria, Hestmark (1991) further argued with reference to thallus morphology that U. nylanderiana is a sister species to the more northern U. arctica which is usually richly fertile with apothecia (teleomorphs) producing sexually generated ascospores.…”
Section: Introductionmentioning
confidence: 94%